Inability to Belch and Associated Symptoms Due to Retrograde Cricopharyngeus Dysfunction: Diagnosis and Treatment. Issue 1 (March 2019) - Bastian, Robert W.; Smithson, Melissa L.
Objective: To propose and test the validity of a new syndrome called retrograde cricopharyngeus dysfunction (R-CPD) that explains inability to belch and the associated symptoms of loud gurgling noises, chest and abdominal pain/distention, and excessive flatulence, as well as to report the results of botulinum toxin (BT) injection into the cricopharyngeus muscle (CPM) for both diagnosis and treatment of R-CPD. Study Design: To develop a case series of consecutive patients matched to the syndromic features of R-CPD, inject the CPM with BT as a concurrent diagnostic and therapeutic maneuver, and assess results. Setting: Bastian Voice Institute (Downers Grove, Illinois). Subjects and Methods: Consecutive (unselected) patients presenting with inability to belch and associated symptoms were matched to the proposed syndrome of R-CPD, treated with BT, and followed for effect on symptoms over time. Results: All 51 patients achieved ability to belch and relief of associated symptoms, and the majority seem to have "retrained" the ability to belch on a potentially "permanent" basis. Conclusion: R-CPD can be diagnosed syndromically, using a symptom complex; clinical diagnosis is validated by relief of symptoms after BT injection; and BT into the CPM is an efficacious treatment, whose benefit appears to often last longer than the pharmacologic duration of action of BT.